Analysis of the Factors of Implementing Qris for Micro Enterprises in Karawang Regency - Muhamad Akmal Demokratsia; Sugeng Budiharsono; Lukman Mohammad Baga (Eduvest - Journal of Universal Studies, 2025)
The transition to the cashless society era influenced micro-businesses to adapt technology in digital payment systems into the process of their transactions. Adoption of QRIS technology becomes a first step for them to enter the digital ecosystem and enhance competitiveness, especially in Karawang Regency. The lack of digital literacy is identified as one of the significant barriers. This research aims to analyze the factors that influence the adoption of QRIS for micro-businesses in Karawang Regency. The analysis method using Multidimensional Scaling Analisis dilakukan menggunakan analisis multidimensional scalling (MDS) through RAPFISH Program. There are three focus dimensions for the analysis, economic, social, and technology. The economy dimension recorded the highest RAPQRIS ordination index score at 64,54687, followed by the technology and social dimensions. Leverage attributes analysis identifies a number of crucial attributes for maximizing QRIS implementation such as cash minimalization, business type, and understanding of supporting application.